Influence of skeletal classes and facial patterns on the positioning of the craniovertebral junction, dimensions of the pharyngeal airway space, and pre-vertebral soft tissue thickness: A cone beam computed tomography study (Research, Society and Development, 2024)
This study employed cone beam computed tomography (CBCT) to assess the influence of skeletal classes and facial patterns on the craniovertebral complex, pharyngeal airway space (PAS) dimensions, and pre-vertebral soft tissue thickness. The analysis of 150 CBCTs involved measurements between various vertebrae and layers of soft tissue. Significant findings included a lower odontoid process in Class II and hyperdivergent individuals, while hypodivergent subjects exhibited a larger area and volume in the PAS. A negative correlation between PAS size and pre-vertebral soft tissue thickness was observed. Gender differences were noteworthy, with males consistently displaying higher values. Significant age-related variations were also identified, with the age groups of 18-30 and 31-45 exhibiting distinct characteristics. The study underscores the impact of facial patterns and skeletal classes on the craniovertebral complex, emphasizing an inverse relationship between PAS and pre-vertebral soft tissue thickness. The intricate connections between gender and age highlight their influence on anatomical characteristics. Understanding how facial patterns and skeletal classes affect the craniovertebral complex has implications for respiratory disorders, including Obstructive Sleep Apnea and Hypopnea Syndrome (OSAHS).